STOCK OPTION PLANS–FULL DISCLOSURE. - Bomeli, Edwin C. (The Accounting Review, 1962)
Abstract In an examination of the 1959 published corporate financial reports of 600 companies in 1960' it was found that 421 or more than 70% referred to an employee stock option plan. It has been asserted in fact that well over 50% of the companies whose stock is listed on the New York Stock Exchange have adopted some form of stock distribution plan for their employees. The courts have permitted stock option plans to be upset by litigation on the part of minority stockholders. One particularly sensitive matter involves developing, recommending, and adopting of stock option plans by parties directly benefiting even if later ratified by the stockholders. Stockholders have some basis at least to judge the adequacy of the consideration given by executives to the corporation. Certainly accountants can do no less than clearly indicate the total consideration given by the corporation and its relative significance. According to the author, no real effort is made to inform the stockholders fully as to the real cost of their managerial services.